2020
DOI: 10.1002/jlb.5hi0420-648r
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: Activation of metabolic nuclear receptors restores periodontal tissue homeostasis in mice with leukocyte adhesion deficiency-1

Abstract: 2 Integrins mediate neutrophil-endothelial adhesion and recruitment of neutrophils to sites of inflammation. The diminished expression of 2 integrins in patients with mutations in the ITGB2 (CD18) gene (leukocyte adhesion deficiency-Type 1; LAD1) results in few or no neutrophils in peripheral tissues. In the periodontium, neutrophil paucity is associated with up-regulation of IL-23 and IL-17, which drive inflammatory bone loss. Using a relevant mouse model, we investigated whether diminished efferocytosis (owi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 82 publications
(264 reference statements)
0
28
0
Order By: Relevance
“…106 Epidermal growth factor itself can also be induced by P. gingivalis, which will contribute to the induction of epithelial-mesenchymal transition, as will transforming growth factor beta 1 and tumor necrosis factor, which are also upregulated by P. gingivalis. 77,107 The interleukin-23/interleukin-17 axis, which regulates homeostasis in the periodontium, 108 is strongly protumorigenic, at least in colorectal cancer. 109 P. gingivalis can incite production of these cytokines, 110,111 although the carcinogenic potential has yet to be investigated.…”
Section: Infl Ammationmentioning
confidence: 99%
“…106 Epidermal growth factor itself can also be induced by P. gingivalis, which will contribute to the induction of epithelial-mesenchymal transition, as will transforming growth factor beta 1 and tumor necrosis factor, which are also upregulated by P. gingivalis. 77,107 The interleukin-23/interleukin-17 axis, which regulates homeostasis in the periodontium, 108 is strongly protumorigenic, at least in colorectal cancer. 109 P. gingivalis can incite production of these cytokines, 110,111 although the carcinogenic potential has yet to be investigated.…”
Section: Infl Ammationmentioning
confidence: 99%
“…In a recent study, the group treated CD18−/− mice with agonists of the transcription factors LXRα/LXRβ (liver X receptors α/β) and PPAR β/δ (peroxisome proliferator-activated receptors β/δ) which are known to promote the resolution of inflammation by the regulation of efferocytosis and neutrophil homeostasis [ 71 , 72 ]. Indeed, pharmacological induction of these receptors resulted in decreased expression of IL-23 and IL-17 and improved bone levels in CD18−/− mice [ 73 ].…”
Section: Druggable Targets In Lad Imentioning
confidence: 99%
“…Of note, Tetsuhiro Kajikawa et al. have shown that impaired efferocytosis, resulting from the loss of β‐integrin (CD18) and the reduction of polymorphonuclear (PMN) recruitment in periodontium, led to an IL‐17/23 axis disorder and caused alveolar bone destruction, 25 suggesting that efferocytosis plays an important role in periodontal tissue homeostasis.…”
Section: The Role Of Mϕs In Periodontitismentioning
confidence: 99%